Older and Wiser: Interpretation of Proverbs in the Face of Age-Related Cortical Atrophy - Kljajevic, Vanja (Frontiers in Aging Neuroscience, 2022)
In the present study, we investigated whether interpretation of proverbs differs across the lifespan and if so, whether it is associated with age-related fronto-temporal atrophy. Using a sample of 333 healthy individuals aged 18-89 years, we found a significant effect of age on proverb interpretation (H (2) = 12.001, p = .002): old adults (OA) were better than young adults (YA) (p = .002), and so were middle-aged-adults (MA) (p = .005). OA and MA had significantly less grey matter (GM) than YA in frontal and temporal lobes bilaterally, and OA less than MA in the right temporal lobe. GM volumes in these regions did not moderate the effect of age on the proverbs scores. The whole-brain analysis of groups’ GM maps revealed that the proverbs scores were associated with more GM in YA relative to OA in the right middle temporal gyrus, which is consistent with evidence on the role of this area in processing of unfamiliar proverbs. Overall, our data suggest that interpretation of proverbs is well preserved in late adulthood, despite considerable age-related cortical atrophy.